The smiling philosopher: Emotional labor, gender, and harassment in conference spaces. Issue 7 (7th June 2019) - Jackson, Liz
Abstract: Conference environments enable diverse roles for academics. However, conferences are hardly entered into by participants as equals. Academics enter into and experience professional environments differently according to culture, gender, race, ethnicity, class, and more. This paper considers from a philosophical perspective entering and initiating culturally into academic conferences as a woman. It discusses theories of gender and emotional labor and emotional management, focusing on Arlie Hochschild's foundational work, and affect in gendered social relations, considering Sara Ahmed's theorization of the feminist killjoy and the affect alien. It applies these lenses to explore problematic experiences of women initiates at conferences. The paper proceeds with a theoretical discussion of gender, emotional labor, and affect. Then the paper discusses women academics' experiences generally and at conferences, including educational research conferences, with reference to relevant higher education research as well as anecdotal evidence, relating these experiences to the theories. It thus aims to tie together theoretical insights, higher education scholarship, and ordinary real-life experiences of gendered social relations in conference activities.